Effect of Good Leadership on Economy as Remedy To Threats To Nation Building: Islamic Perspective From the Life of Umar Ibn Abdul Aziz - Alhaji Isa, Ibrahim; Onuweh Jimoh, Isah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The effect of negative practice of democracy on the economy of any society acts a great threat to nation building. Nigeria has been faced with economic crisis since the return of democracy in 1999. This is as a result of the way by which the political leaders who are in the helm of affairs handled its economic system. The level of poverty in the land results in social ills such as kidnapping, arm robbery, political thuggery, fornication and adultery which act as a threat to the nation. Therefore, the need for this study ‘Effect of Good leadership on Economy as Remedy to threats to Nation Building: Islamic Perspective of Umar ibn Abdul Aziz’. Qualitative method is used through content analysis of both primary and secondary literatures. The study contributes to leadership and good governance by highlighting the principles applied by this pious predecessor that resulted in achieving a golden age of governance that is still reckoned with till date. Such principles includes Tauhid as the first step in establishment of leadership as first step of his leadership; sticking to the practice of the Prophet as guides; Justice (Adl), Accountability (Hisab), Responsibility/Consultation (Shurah) and Social welfare (Maslahah) among others; .Suggestions are given for remedying the present threats to the nation as exemplified by Umar ibn Abdul Aziz whose situation at his inauguration looked the same with that of Nigeria. The suggestions includes Sticking to tauhid in ones leadership being grounded in knowledge, following the foot steps of the Prophet as guide, upholding Justice, fairness, accountability irrespective of tribe or religion among others.